2011
DOI: 10.1080/10590501.2011.601848
|View full text |Cite
|
Sign up to set email alerts
|

A Current Global View of Environmental and Occupational Cancers

Abstract: This review is focused on current information of avoidable environmental pollution and occupational exposure as causes of cancer. Approximately 2% to 8% of all cancers are thought to be due to occupation. In addition, occupational and environmental cancers have their own characteristics, e.g., specific chemicals and cancers, multiple factors, multiple causation and interaction, or latency period. Concerning carcinogens, asbestos/silica/wood dust, soot/polycyclic aromatic hydrocarbons [benzo(a) pyrene], heavy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 80 publications
0
67
0
5
Order By: Relevance
“…Industrial wastewaters contain a complex range of organic pollutants including dyes, detergents, oils, and other organic compounds (8), some of them being carcinogenic and exhibiting other side effects (9). Domestic wastewater is also not considered innocuous and often contains trace levels of pharmaceuticals and personal care products (PPCPs) (10) among others (11).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial wastewaters contain a complex range of organic pollutants including dyes, detergents, oils, and other organic compounds (8), some of them being carcinogenic and exhibiting other side effects (9). Domestic wastewater is also not considered innocuous and often contains trace levels of pharmaceuticals and personal care products (PPCPs) (10) among others (11).…”
Section: Introductionmentioning
confidence: 99%
“…Total 140 patients were interviewed in two months of data collection where male and female ratio was 1:1. A similar study was done at the National Institute of cancer research and hospital (NICHR) in 2006 [33,34]. In this study, data was first analyzed in univariate approach and then multivariate approach (using partial least square path model).It has been observed that the highest number (54.23%) of patients were in 41-60 years age group, followed by 33.38% in 21-40 years age group [22].…”
Section: Discussionmentioning
confidence: 99%
“…Los colorantes son compuestos altamente coloreados y difíciles de descomponer biológicamente [1], los desechos de pigmentos en aguas residuales se consideran un tipo de contaminante objetable debido a su alta toxicidad tanto para el ecosistema como para la salud humana [2]. Esto ha creado una gran preocupación medioambiental acerca de las condiciones de los cuerpos de agua, lo que ha llevado a la necesidad de buscar técnicas eficaces para remover estos pigmentos de los efluentes y solucionar los problemas de contaminación [3].…”
Section: Introductionunclassified